Characterization of porcine aortic valvular interstitial cell 'calcified' nodules - Cloyd,KL; El-Hamamsy,I; Boonrungsiman,S; Hedegaard,M; Gentleman,E; Sarathchandra,P; Colazzo,F; Gentleman,MM; Yacoub,MH; Chester,AH; Stevens,MM (PLOS One, 2012)
Valve interstitial cells populate aortic valve cusps and have been implicated in aortic valve calcification. Here we investigate a common in vitro model for aortic valve calcification by characterizing nodule formation in porcine aortic valve interstitial cells (PAVICs) cultured in osteogenic (OST) medium supplemented with transforming growth factor beta 1 (TGF-β1). Using a combination of materials science and biological techniques, we investigate the relevance of PAVICs nodules in modeling the mineralised material produced in calcified aortic valve disease. PAVICs were grown in OST medium supplemented with TGF-β1 (OST+TGF-β1) or basal (CTL) medium for up to 21 days. Murine calvarial osteoblasts (MOBs) were grown in OST medium for 28 days as a known mineralizing model for comparison. PAVICs grown in OST+TGF-β1 produced nodular structures staining positive for calcium content; however, micro-Raman spectroscopy allowed live, noninvasive imaging that showed an absence of mineralized material, which was readily identified in nodules formed by MOBs and has been identified in human valves. Gene expression analysis, immunostaining, and transmission electron microscopy imaging revealed that PAVICs grown in OST+TGF-β1 medium produced abundant extracellular matrix via the upregulation of the gene for Type I Collagen. PAVICs, nevertheless, did not appear to further transdifferentiate to osteoblasts. Our results demonstrate that ‘calcified’ nodules formed from PAVICs grown in OST+TGF-β1 medium do not mineralize after 21 days in culture, but rather they express a myofibroblast-like phenotype and produce a collagen-rich extracellular matrix. This study clarifies further the role of PAVICs as a model of calcification of the human aortic valve.